CURRENT ISSUES OF IMPROVING THE PROTECTION OF INTELLECTUAL PROPERTY AT THE INTERNATIONAL LEVEL - Mukumov, Bobur (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2024)
In this article, the issues of the influence of international intellectual property documents on this area will be considered on the example of some foreign countries. Let's highlight the countries of the Anglo-Saxon legal system (first of all, the United Kingdom and the United States). The internal legislation of the countries of this group has its own individual characteristics. Based on the generalization of judicial precedents, we can identify particular codifications.